What's up with Witch Rings?. (January 2015) - Heard, Priscilla; Phillips, David
'Witch rings' are well-known novelty rings that show a size-change illusion when rotated. We have replicated the illusion of expansion of the reflections in the rings in a variety of contexts with animations, though not as yet so successfully imitated the sense that the whole ring expands and contracts.